SUBOPTIMAL LAND MANAGEMENT TO INCREASE RICE PRODUCTIVITY - Ali Jamil; Nurhayati (International Journal of Economic, Business, Accounting, Agriculture Management and Sharia Administration (IJEBAS), 2026)
Suboptimal land is a strategic resource with great potential to support increased rice production in Indonesia amidst the increasingly limited area of productive rice fields due to land conversion, environmental degradation, and the pressures of climate change. This land includes acidic drylands (Ultisols and Oxisols), tidal swamps, lowlands, peatlands, saline lands, and other marginal lands that face various constraints, such as high acidity levels, low soil fertility, aluminum (Al) and iron (Fe) poisoning, salinity, and limited water availability. Various research results published in accredited national journals and reputable international journals show that rice productivity on suboptimal land can be increased through the implementation of integrated land management. These strategies include the use of ameliorants such as lime, dolomite, biochar, and gypsum to improve soil chemical properties, the addition of organic matter to improve the physical and biological quality of the soil, the application of balanced fertilization based on location specific, the use of rice varieties adaptive to environmental stress, efficient water management, and the use of biofertilizers and functional microorganisms to increase nutrient uptake efficiency. In addition, the development of sensor-based precision agriculture technology, the Internet of Things (IoT), remote sensing, drones, and artificial intelligence ( AI ) opens up new opportunities for more effective and sustainable land management. This review article aims to synthesize the results of recent research on suboptimal land management to increase rice productivity, identify research gaps , and formulate directions for the development of technology that is adaptive to climate change. The results of the study indicate that the application of integrated management technology can increase rice productivity, improve soil quality, increase input efficiency, and support the creation of a sustainable and climate-resilient rice production system.